Test de charge de la durabilité urbaine : Le cas de « l’écoquartier exemplaire » de la zone de l’Union (Nord, France) - Caroline Lejeune; Bruno Villalba (VertigO)
The Union, the former industrial territory, the intermunicipal space of the cities of Tourcoing, Roubaix, Wattrelos, been the object of an urban rehabilitation on a territory in situation of poverty. Indicated in the 2000s, economic center of excellence of Lille Métropole Communauté urbaine ( LMCU), it is elected experimental ecodistrict of the Lille metropolis in 2006 according to the application of the Schedule(Diary) 21 community. The integration of the durability on a pauperized territory allows to seize modalities of adaptation of an urban project to the ecological crisis. How does the strategic planning of the ecodistrict take into account thresholds of irreversibility of the ecological crisis? The territorial public policies of development it integrate the uncertainty and the environmental urgency into the urban adaptation of the lifestyles? The test of load on the urban durability of the territory will contribute to estimate certain number of tensions (participative, social, ecological, territorial) in the capacity of the territory to resist the ecological shock.